Coupling optimization of composite insulation and vapor-cooled shield for on-orbit cryogenic storage tank. (December 2018) - Jiang, W.B.; Zuo, Z.Q.; Huang, Y.H.; Wang, B.; Sun, P.J.; Li, P.
Highlights: Insulation performance of Foam/VCS/VD-MLI combination are investigated for LH2, LN2, LO2 and LCH4 tanks. VCS promotes heat flux reduction of cryogenic tanks. The optimal position of VCS locates at middle of the VD-MLI's thickness. VCS is particularly suitable for LH2 tanks. Abstract: The long-term storage of cryogenic propellants on orbit under thermal and pressure control is a promising enabling technology for future space exploration. Composite insulation composed of polyurethane foam (Foam), variable density multilayer insulation (VD-MLI), and a vapor-cooled shield (VCS) is considered as an effective passive thermal control method for such missions. This paper presents a theoretical model that considers three heat transfer mechanisms simultaneously within the VD-MLI and convective heat transfer inside the VCS, to predict and optimize the thermal performance of the insulation combination. The model is validated by experimental data. The influences of VCS position and warm boundary temperature (heat flux) on the thermal insulation performance are investigated for LH2, LN2, LO2, and LCH4 tanks. The temperature profiles within the insulation material with or without VCS are compared. In addition, the contributions from the VCS to reduce the heat flux into the tank are evaluated. The conclusions are valuable for the optimal design of future composite insulation with Foam/VCS/VD-MLI for cryogenic storage tanks on orbit.